Pavilion 22 . The Zagreb Fair - Puhovski, Nenad (Factum, 2002)
Duration: 00:52:00 The film is about fully unknown and dark side of the happenings that took place within the Zagreb Fair compound in the autumn of 1991, the year in which the war broke out. First established as a mobilisation center of police reserve forces, it soon became a transit camp and persecution center. By interviewing some of the involved actors and also using archival footage, the director attempts to shed some light over the events related to Pavilion 22 and their signification in the context of the recent history of Croatia.